Measures to Maintain a SARS-CoV-2 Negative Inpatient Hematological Unit in the Midst of the COVID-19 Pandemic - Cabero-Martínez, Almudena; Sánchez-Guijo, Fermín; López-Corral, Lucía; Pérez, Estefanía; Avendaño, Alejandro; Baile, Mónica; Cabrero, Mónica; Martín, Ana-Africa; Rodríguez, Angela; Pérez, Balbina; Peña-Muñoz, Felipe; Román, Luz-Gema; et al. (Frontiers in Medicine, 2020)
The University Hospital of Salamanca, in Spain, had its first COVID-19 case on March 1st and as of May 11th, we had 1,100 positive cases. Based on the vulnerability of patients with blood cancers, on March 9th, the Hematology Department developed a protocol, amended as the new information was available, to maintain the Hematology Unit as a “free COVID-19 island”. The protocol included symptom-based surveys and screening tests to patients, caregivers and healthcare personnel to identify early potential positive cases and prevent its spread. Between March 9 and April 28, 32 asymptomatic patients and caregivers were tested and 68 rT-PCR diagnostic assays have been performed with two positive results. A hundred and six healthcare workers have been tested (208 rT-PCR) and seven of them were positive. In summary, the implementation of preemptive measures after the first case appeared allowed us to be able to provide treatment to our patients.